To ascertain the implementation of the plastic carrier bags regulations at the local government sphere in Gauteng Province - Ndzhukula, Sizakele Judith (My University, 2012)
There has been a genuine problem with plastic carrier bags (PCBs) pollution since the 1970’s. A literature review revealed that very few scientific studies have been undertaken globally on PCB. The South African Government promulgated regulations to reduce numbers, encourage reuse and recycling of plastic bags in 2003. The regulations introduced a charge for PCBs. This study looked at the handling and disposal of PCB after 2003 in Gauteng Province, South Africa; and looked at the movement of PCB from major retailers and informal traders to consumers and recycling and recovery. The study excluded the manufacturers and distributors of PCB. It began with the retailers and informal traders being the source of PCB and extended to consumers during their grocery shopping in large retail stores and purchases from informal traders. The study also looked at the individual waste collectors operating in landfill sites, residential and industrial areas to establish the level of recycling of PCB. Buyisa-e-Bag (B-e-B) was at the end of the collection of PCB pathway where it was supposed to provide leadership in the recovery of the bags. Semi-structured interviews were used to collate data on recycling approach with specific focus on PCB and understanding of the legislation. A total of one hundred consumers were interviewed in the shopping malls. Consumers did not know much about the regulations hence they could not explain the reason they have to pay for PCB. Ninety one percent of consumers did not reuse bags for shopping and 68% reused PCB at home to store waste before it is disposed of. Eighty informal traders were interviewed: all indicated that they did not charge for PCB. Forty chain supermarkets managers were interviewed from the shopping centres covered by the study. The retailers were affected by the PCB regulations; they reduced the number of grocery packers and increased security to prevent theft. Nevertheless, they complied with the regulations by selling only the thick bags. Twenty landfill and recycling facilities managers formed part of the study. All landfill managers encouraged general waste recycling to prolong lifespan of the site. Fifty individual recyclers were interviewed in the landfill sites, recycling facilities and on the road side while pushing their trolleys. They found it economically impractical to collect PCBs. Awareness of plastic litter has increased and less is visible though this was not measured. Legal compliance with regulations and specifications needed to be actively driven by all the relevant parties. PCBs are fully recyclable; hence more public awareness is required aimed at preventing the contamination of bags which deters re-claimers from collecting them. B-e-B has not met most of the objectives of their formation and has since been placed under administration by DEAT. Inadequate communication and collective bargaining between the key role parties resulted in the delays in getting the recycling projects off the ground. Major retailers complied with the Government regulations. Informal traders and consumers were generally unaware of regulations and consequences of PCB use. Consumers bought new PCB and in most cases, failed to reuse them for shopping. Recycling of PCBs is not carried out effectively as it is not economically worthwhile. This requires further research to explore the potential uses of PCBs at the end of their lifecycle
M.Sc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: Recycling (Waste, etc.); Plastic scrap; Polyethylene